ANALISIS EFEKTIVITAS PENGGUNAAN ABSENSI ELEKTRONIK (E – ABSENSI) PADA SMKN 1 SIDRAP - Muhammad Hidayat L; Wardimansyah Ridwan (STKIP Paris Barantai, 2023)
This study aims to determine the effectiveness of using electronic attendance at SMKN 1 Sidrap. This research is a descriptive qualitative research, the data source utilizes primary data and data collection through interviews with informants. The results of the interviews were analyzed using the observing and note-taking methods. The results of the study on the Effectiveness of Using E-Absence are measured through indicators measuring program effectiveness including effort, cost efficiency, results, cost effectiveness and impact. Based on program effectiveness, the effectiveness of the E - Attendance application at SMKN 1 Sidrap includes school management efforts in procuring E - Absence, there is cost efficiency in running the E - Absence program, the expected results are achieving the target of increasing the discipline of Students and Educators in the learning process, the resulting cost-effectiveness has a positive impact on budget management, and a long-term impact on the procurement of E - Absenteeism to increase the effectiveness of learning and use of the school budget. Keywords: Effectiveness, E-Absence, Electronics.